Abundance and Distribution Patterns of Gastropods in the Intertidal Bay of Kambang Lengayang Sub-District, Southern Coastal District, West Sumatera - Harif, Ichwanul; Tanjung, Afrizal; Elizal, Elizal (Jurnal Natur Indonesia, 2021)
This study aims to determine the abundance and distribution pattern of gastropods in the intertidal bay, Kambang Lengayang District, Pesisir Selatan Regency, West Sumatra. The benefits of this research are expected to be a reference or information for further research in Kambang Bay which in the end is expected to minimize the adverse effects of gastropod hunting. The research method used in this study is a survey method, namely direct observation and sampling which is divided into 3 stations where the sampling station 1 is taking in the coastal waters of the bay in an area where there is no community activity, station 2 is taking in the waters of the bay in the fishing trawl area. station 3 taking in the coastal waters of Kambang in the reclamation area. Based on the analysis of organic sedimentary material in the study area, the average value was obtained at station 1 (3.55%), station 2 (4.20%) and station 3 (3.33%). Based on the analysis, the sediment fraction that dominates each station is sand. The gastropods found at the study site were Clypeomorus bifasciata, Littoraria scabra and Cerithulata cingulata. The abundance of gastropods in the coastal waters of Kambang ranged from 2.33 to 5.00 Ind/m2. The results of the ANOVA test showed that the abundance of gastropods in the bay waters showed 0.214 beaches, indicating that the difference in abundance between stations was not significant. The gastropod pattern found at the study site is generally in groups.